Student debt and hardship: Evidence from a large sample of low- and moderate-income households. (November 2016) - Despard, Mathieu R.; Perantie, Dana; Taylor, Samuel; Grinstein-Weiss, Michal; Friedline, Terri; Raghavan, Ramesh
Abstract: Student debt has risen in recent years as higher education costs have shifted to students and their families, particularly those with low-to-moderate incomes (LMI). Though a college degree continues to convey higher earnings, those who finance their degrees have lower net worth and greater financial difficulties than persons without student debt. We assess the relationship between student debt and material and health care hardship among a large sample ( n = 5558) of LMI tax filers, using propensity score analysis to adjust for self-selection into student debt status and loan amount and monthly payment quartiles. We find that participants with student debt have a higher likelihood of hardship. Loan amounts only partially predict hardship, and borrowers making current loan payments are at lower odds for hardship than non-payers. We also find that among those with student debt, non-payers and those without college degrees have much greater social and economic disadvantages. Highlights: Student debt is associated with greater hardship and financial difficulty. Higher loan amounts are only associated with health care hardship. Monthly repayment amounts are not associated with hardship or financial difficulty. Participants making re-payments have social and economic advantages. Not finishing college is associated with hardship and economic disadvantage.